Daily changes on seasonal ecophysiological responses of the intertidal brown macroalga Lessonia spicata: Implications of climate change - Celis-Plá, Paula S. M.; Trabal, Andres; Navarrete, Camilo; Troncoso, Macarena; Moenne, Fabiola; Zúñiga, Antonio; Figueroa, Félix L.; Sáez, Claudio A. (Frontiers in Plant Science, 2022)
Global climate change is expected to have detrimental effects in coastal ecosystems, with impacts observable at local and regional levels, depending on factors such as light, temperature and nutrients. Shifts in dominance between primary producers that can capitalize carbon availability for photosynthesis will have knock-on effects on marine ecosystems, affecting their ecophysiological responses and biological processes. Here, we study vulnerability, photoacclimation capacity, and tolerance responses as ecophysiological responses of the intertidal brown macroalga Lessonia spicata (Phaeophyceae, Laminariales) during a year through the different seasons (Autumn, Winter, Spring and Summer) in Pacific Ocean (Chile). Six different daily cycle experiments were carried out within each season. A battery of different biochemical assays associated with antioxidant responses, and in vivo chlorophyll a fluorescence parameter, showed that at Spring- and Summer-times there was an increase in photosynthetic capacity in the macroalga, although their responses varied depending on light and nutrient availability along to the year. L. spicata showed the maximal photosynthesis and similar photoinhibition pattern in summer compared to other seasons in spite the contents of nitrate and phosphorous in seawater were less that winter-time. Thus, high irradiance at Spring- and Summer-times, displayed higher maximal electron transport rate (ETRmax), Irradiance of saturation (Ek), Non-photochemical quenching (NPQmax), nitrogen and carbon contents, photoprotectors compound levels. Antioxidant activity increased also in summer, seasonal period with the highest oxidative stress conditions, i.e., highest level of hydrogen peroxide (H2O2). In contrast, under low irradiance, i.e., wintertime conditions, L. spicata demonstrated lower concentration of the photosynthetic pigments as Chla and carotenoids. Our study suggests that macroalgae that are subjected to increased irradiance and water temperature under lower nutrient availability mediated by seasonal changes (expected to worsen under climate change), respond with higher values of productivity, pigments content and photoprotective compounds. Thus, our findings strengthen the available evidence to predict that brown macroalgae could better proliferate, with lower vulnerability and greater acclimation, that other marine species subject to the future expected conditions associated with climate change.